Dual ballot effects on French presidential vote choice. (February 2019) - Bélanger, Éric; Turgeon, Mathieu
Abstract: Relatively little is known about how voters behave under dual ballot voting systems. Do voters follow different decision rules at each ballot? Do they weigh relevant considerations differently on the second ballot, as compared to the first ballot? Does political sophistication condition the way people vote on the first and second ballots? Using survey data from five French presidential elections, we examine these questions and find that voters in France do indeed treat first and second ballots differently. More precisely, we find that both partisanship and ideology matter more on the second ballot. Demographics, socioeconomic status, and political issues, on the other hand, weigh more heavily in the first round. Political sophistication, for its part, does not condition nor reinforce these effects.